Significance and comparative analysis of tourist internet platforms booking and Airbnb - Sran Maričić; Irijana Rajkovic; Dino Baricevic (UTMS Journal of Economics, 2023)
Internet platforms significantly facilitate the travel and stay of users. In Europe and the United States, the most widely used platforms are Booking and Airbnb and this paper will provide their comparative analysis of each other. Both platforms use advanced information technologies, such as artificial intelligence and/or recommendation algorithms, to facilitate travel planning and destination selection. Both Booking and Airbnb use machine learning algorithms to analyze data on previous searches and user characteristics. Based on this information, they provide personalized searches and accommodation recommendations or activities that may be of interest to the user. Both platforms also offer user feedback, which is significant in building trust among users and in improving services globally. This paper will analyze key parameters that are taken into account when choosing a tourist service, such as price, location, ratings and reviews, as well as market analysis of these two platforms.
Keywords: L83; Z32; I15; O18; 330; Booking; Airbnb; tourism; information technology; artificial intelligence; market